Kuat Tekan Beton Geopolimer dengan Variasi Penambahan Limbah Las Karbit - Muhrodi, Muhrodi; Saputro, Yayan Adi; Umam, Khotibul (Portal: Jurnal Teknik Sipil, 2024)
The addition of carbide waste is an effort to increase the calcium element needed in the occurrence of pozzolanic reactions when mixed with SiO2 in carbide waste. The pozzolanic reaction is a reaction between calcium, silica or aluminate with water to form a hard and stiff mass which is almost the same as the hydration process in Portland cement. the effect of carbide waste on the compressive strength of concrete, and can reduce the use of Portland cement in the concrete mix and make optimal use of carbide waste. This research was carried out by replacing a certain percentage of the weight of cement with carbide welding waste. Concrete is printed using cylindrical molds measuring 20 cm high with a diameter 10 cm. The test was carried out when the concrete reached the age of 21 days. The test carried out was a compressive strength test using a Compression Testing Machine in the Construction Materials Technology Laboratory, Civil Engineering Department, FST, Nahdlatul Ulama Islamic University, Jepara.